Preliminary estimation of Sunda Scops Owl home range in an isolated forest - Zolkanain, Nornajmi Hanis; Puan, Chong Leong; Pilla, Phillcaine; Hussin, Mohamed Zakaria (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The patterns of spatial usage by animals are often associated with their morphological, physiological and behavioural adaptations to environmental changes. The spatial requirements of most owl species in Malaysia are little known. This paper presented the preliminary results on the home range of Sunda Scops Owl (Otus lempiji) based on the radio-telemetry method conducted in the Ayer Hitam Forest Reserve, Puchong. The home range size of a single male owl based on 95 % Mean Harmonic calculation was 0.57 ha. The core area size based on 50 % Mean Harmonic calculation was 0.22 ha. After nine nights of tracking, one roosting site within the home range was identified. A better understanding of home range and ranging behaviour of a species such as owls is essential in their conservation as well as the management of protected areas.